Novel Approach of Biodiesel Production Waste Utilization to Support Circular Economy in Biodiesel Industry. Issue 1 (April 2021) - Choirun Az Zahra, Aghietyas; Arina Rusyda, Ilya; Hizbiyati, Andini; Giovani, Felix; Zahara, Nabila; Jiwandaru, Bramantha; Gunawan, David; Andre Halim, Giovani; Pratiwi, Meiti; Nur Istyami, Astri; Verani Rouly Sihombing, Atmy; Harimawan, Ardiyan; et al.
Abstract: Current development of industry nowadays is more towards sustainability and greener production that minimize the production of waste, for example the production of biodiesel energy from Refined, Bleached, and Deodorized Palm Oil (RBDPO). However, biodiesel production is still could not eliminate the hazardous waste that is glycerin pitch. Glycerin pitch is a waste found in the glycerin purification unit which is a unit used to produce the high-grade glycerin, a side product of biodiesel production. Up until now, the existing glycerin pitch is still not well managed and remains as a hazardous waste. Glycerin pitch contains a sodium salt that can be recovered to produce biodiesel transesterification catalyst, sodium methoxide. Applying a concept of circular economy, a catalyst recovery building block is attached to integrated biodiesel process with glycerol purification. The process consists of three units, solid-liquid extraction to separate inorganic salt contains in the pitch, Chlor-Alkali process to convert inorganic sodium salt to sodium hydroxide, and catalyst making reactor to produce a sodium methoxide. Using a simulation process, the amount of catalyst recovered in the process is 43.78%.